Development and Characterisation of Polyherbal Phyto-Somal Gel for Wound-Healing Activity - Rai, Neeta (Asian Journal of Pharmaceutics (AJP), 2025)
The global demand for herbal-based cosmetic products has increased because they have a lower risk of side effects compared to synthetic items. Natural remedies are increasingly valued for their effectiveness in healing wounds. Objectives: This study aims to develop and characterize a polyherbal phytosomal gel that includes Singapore daisy (Sphagneticola trilobata) leaf extract and Hibiscus rosa-sinensis flower extract. The goal is to explore their combined potential for wound healing, reducing inflammation, and fighting bacteria. Methods: Three formulations (F1, F2, F3) were created with different concentrations of the two herbal extracts. These gels underwent tests to evaluate their physical and biological properties, such as appearance, pH, viscosity, solubility, skin irritation, acid content, saponification value, consistency, ease of removal, and phase separation. Results: All formulations showed good physical stability. Among them, Formulation F3 displayed the best features, with no signs of redness, swelling, or irritation when applied to the skin. The phytosomal system improved the stability and effectiveness of the extracts. Conclusion: The polyherbal gel, especially Formulation F3, is a strong candidate for safe and effective wound healing. This study supports the use of herbal extracts in modern cosmetic products and opens the door for further clinical research.